Comorbidities in recent-onset adult type 1 diabetes: a comparison of German cohorts - Zaharia, Oana-Patricia; Lanzinger, Stefanie; Rosenbauer, Joachim; Karges, Wolfram; Müssig, Karsten; Meyhöfer, Sebastian M.; Burkart, Volker; Hummel, Michael; Raddatz, Dirk; Roden, Michael; Szendrödi, Julia; Holl, Reinhard W. (Frontiers in endocrinology, 2022)
AimsRestrictive exclusion criteria from different study populations may limit the generalizability of the observations. By comparing two differently designed German cohorts, we assessed the prevalence of cardiovascular risk factors and diabetes-related complications in recent-onset adult type 1 diabetes.MethodsThis study evaluated 1511 persons with type 1 diabetes of the prospective diabetes follow-up registry (DPV) and 268 volunteers of the prospective observational German Diabetes Study (GDS) with a known diabetes duration <1 year. Participants had similar age (36 years), sex distribution (41% female) and BMI (26 kg/m2) in both cohorts.ResultsThe average HbA1c was 6.4 ± 0.8% in the GDS and 7.0 ± 1.1% in the DPV. Prevalence of hypertension (24%) was similar, while more DPV participants had dyslipidemia and lipid-lowering medication than GDS participants (77% vs. 41% and 7% vs. 2%, respectively; p<0.05). Prevalence of retinopathy and nephropathy was higher in DPV compared to GDS participants (10% vs. 3% and 18% vs. 7%, respectively; p<0.001).ConclusionsDiabetic nephropathy and retinopathy are the most frequent complications in type 1 diabetes, affecting up to every 10th patient within the first year after diagnosis, underlining the need for more stringent risk factor management already at the time of diagnosis of type 1 diabetes.
Gesehen am 26.08.2022